Hubungan Infeksi Soil Transmitted Helminths (STH) Dengan Status Gizi Dan Anemia - Butar-butar, Kristin; Julianto, Endy; Pinta Omas Sinurat, Puji (Jurnal Kedokteran Methodist, 2021)
Background: Soil Transmitted Helminths (STH) is the most well known infectious disease. The types of worms that commonly infect are Ascaris lumbricoides, Trichuris trichiura, Necator americanus, and Ancylostoma duodenale. The spread of intestinal infections is highest at the age of children and susceptible to the effects of worm disease. Method : The method used is a research using the method of literature review or literature review. Conclusion: It can be concluded that there is no relationship between STH infection with nutritional status and anemia in elementary school children.